Collis-Nissen gastroplasty and fundoplication method for the very long gap esophageal atresia in children - Mačiulytė, Rūta; Gurskas, Pranas; Trainavičius, Kęstutis; Kaupienė, Milda (Lietuvos chirurgija, 2017)
Objective The purpose of this study is to evaluate the modified Collis-Nissen gastroplasty and fundoplication method in children with a very long gap esophageal atresia. Methods During the period of 1996–2016 years there were 151 patients having esophageal atresia and 23 patients had a long gap esophageal atresia were treated in our hospital. 3 patients had a very long gap esophageal atresia and the Collis-Nissen late esophagoplasty were performed. The remote results were observed retrospectively from the outpatient charts. Results Three boys who were born at the gestational age of 35, 35 and 37 weeks within the first few hours were diagnosed having type B, C and C esophageal atresia. Two of these patients had surgeries on their first day and the third patient was operated on his second day. The closure of tracheoesophageal fistulas and gastrostomy were performed for all of these newborns, the sigmostoma – for one patient. They were diagnosed having a very long gap (diastasis at 7, 4 and 6 cm) esophageal atresia. Before the Collis-Nissen gastroplasty and fundoplication was performed, the esophagus was elongated till the patients were 7, 7 and 4 months old. All of the boys experienced early and late complications: anastomosis leaking, mediastinitis, sepsis, scarring stenosis have occurred, but remediastinotomies, drainages of mediastinum, dilatations of esophagus were successful. All three patients quickly were able to eat normally. Records in the outpatient charts show the boys having no complaints, eating well, having a good appetite. Conclusion Collis-Nissen esophagoplasty is a good alternative comparing with other surgical reconstructions when dealing with a very long gap esophageal atresia.